Pengaruh Media Sosial terhadap Perilaku Konsumen dalam Pembelian Online di Kalangan Generasi Z pada Platform E-Commerce Shopee - Nur Pratama Julianto; Natal Indra (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study aims to analyze the influence of social media on consumer behavior in online purchases among Generation Z, focusing on the Shopee e-commerce platform. Generation Z, which is the age group born between 1997 and 2012, is known to be an active social media user, which influences their purchasing decisions. Through a survey conducted on Shopee users from Generation Z, this study identified factors that influence consumer behavior, including the influence of advertising, product reviews, and interactions with influencers on social media. The results of the study show that social media plays a significant role in shaping the preferences and purchasing decisions of Generation Z. Interesting advertisements and positive reviews from other users on social media can increase purchasing interest, while interactions with influencers can provide additional trust in the products offered. This study provides important insights for marketers to design effective and relevant marketing strategies with Generation Z consumer behavior in the digital era.